A Biased-Randomized Heuristic for the Waste Collection Problem in Smart Cities - Contreras-Bolton, C (Springer Verlag, 2018)
This paper describes an efficient heuristic to solve the Waste Collection Problem (WCP), which is formulated as a special instance of the well-known Vehicle Routing Problem (VRP). Our approach makes use of a biased-randomized version of a savings-based heuristic. The proposed procedure is tested against a set of benchmark instances, obtaining competitive results. © Springer International Publishing AG, part of Springer Nature 2018.